The Degree of Availability of Grammatical Concepts in the Books of "Arabic Is My Language " for The basic fifth and sixth grade and Third Level of "B" curricula according to National Standards (Journal of Hama University, 2024)
This research aims to determine grammatical concepts included in "Arabic Is My Language" curricula's content to the fifth and sixth basic grade and "Arabic Is My Language" for the third level of "B" curricula according to national standards in Syrian Arab Republic, and discover grammatical concepts, correlation level in content of "Arabic Is My Language" curricula's to the fifth and sixth basic grade and "Arabic Is My Language" for the third level of "B" curricula.For these aims: Descriptive analytical method used by using: a list of grammatical concepts according to Syrian national standards and content analysis form and checking its validity and reliability. The list included: (4) grammatical concept to the fifth basic grade,(10) grammatical concept to the sixth basic grade ,and (14)grammatical concept to the third level of "B" curricula.The research revealed to group of results according to Syrian national standards, the most important of it:- There are grammatical concepts in grammatical books to the fifth and sixth basic grade with (76%).- There are grammatical concepts in science books to the third level of "B" curricula with (73%).- There is a strong correlation between "Arabic Is My Language" books, content to the fifth and sixth basic grade and "Arabic Is My Language" book's content to the third level of "B" curricula according to grammatical concepts included in national standards document in Syrian Arab Republic